Geological tectonics and physio-chemical metrics as screening criteria for MEOR applicability in West Africa transform regional oil wells - a review. (2018) - Ansah, Eric O.; Sugai, Yuichi; Sasaki, Kyuro
Primarily, most oil wells in the West Africa transform region are produced using water or water alternating gas. This is believed to be unsustainable going forward. Also, though the region contributes less to global greenhouse emission, global warming effects in the region cannot be undermined. Microbial enhanced oil recovery (MEOR) has been proven worldwide to be environmentally friendly as well as less costly to develop. Despite the advantages of MEOR over other oil recovery methods, operating companies in the region are yet to apply this bespoke technology. Therefore, this study reviews the potential applicability of MEOR process to West African oil fields comparing the geology and physiochemical properties to major oil fields in South America (where MEOR has been previously applied). Applying MEOR in the region could be a major step towards improving production of new oil wells and enhancing sustainability of old oil wells.